'A Good Head and a Better Whip': Ireland, Enlightenment, and the body of slavery in Marlon James's The Book of Night Women. (2nd July 2016) - Forter, Greg
ABSTRACT: In Marlon James's neo-slave narrative, The Book of Night Women (2009), an Irish overseer embodies both the most hegemonic expression of colonial Enlightenment and the utopian promise of an alternative kind of Enlightenment futurity. This article explores both of these linkages. It brings to bear Luke Gibbons's concept of the 'sympathetic sublime' in order to do so and demonstrates the strengths and limitations of a politics based in the Irishman's sympathetic identification with the suffering black body. It emphasizes the radical potential of such sympathy while indicating that affective politics requires the supplement of a cognitive grasp of slavery as a system of domination and labor exploitation.